Effect of Different Feed Restriction Regimes During the Starter Stage on Productivity and Carcass Characteristics of Male and Female Ross 308 Broiler Chickens - Novel, D.J.; Ngambi, J.W.; Norris, D.; Mbajiorgu, C.A. (International Journal of Poultry Science, 2008)
An experiment was conducted to determine the effect of different feed restriction regimes during the starter stage (14-21 days) on productivity and carcass characteristics of male and female Ross 308 chickens. A 3 (feeding levels: ad-libitum intake, 50% ad-libitum intake and 75% ad-libitum intake) x 2 (male and female chickens) factorial arrangement in a complete randomized design was used. Feed restriction affected (p<0.05) live weight of chickens at the age of 21 days and male chickens were heavier (p<0.05) than females at the same age. Chickens on 75% ad libitum feeding attained complete compensation in live weight at 42 days of age while those on 50% ad libitum feeding did not. However, male chickens attained higher (p<0.05) live weights than female chickens at 42 days of age. It is suggested that 75% ad libitum restriction feeding during the starter stage from 14 up to 21 days of age may offer some economic advantage over ad-libitum feeding regimen, mainly by enhancing feed utilization. It may, therefore, be a useful nutritional strategy to reduce the cost of commercial starter grain based-diets.